A systematic review to identify whether perfusate biomarkers produced during hypothermic machine perfusion can predict graft outcomes in kidney transplantation - Guzzi, F; Knight, S; Ploeg, R; Hunter, J (Wiley, 2020)
There is good evidence to support the use of hypothermic machine perfusion (HMP) over static cold storage as the favoured preservation method for deceased donor kidneys. However, the utility of HMP as a tool to assess the viability of kidneys for transplant is unclear. There is a need to determine whether perfusate biomarkers produced during HMP can predict post‐transplant outcomes and assess the suitability of organs for transplantation. Three different databases (MEDLINE, Embase, Transplant Library) were screened to 31 May 2019. Articles were included if a relationship was reported between one or more perfusate biomarkers and post‐transplant outcomes. Studies were assessed and graded for methodological quality and strength of evidence. Glutathione S‐transferase was the most promising biomarker for predicting delayed graft function, but its predictive ability was at best moderate. Analysis of primary nonfunction rates was challenging due to low occurrence rates and small sample sizes. Existing studies are limited in quality and have not yielded biomarkers for kidneys undergoing HMP that are able to predict post‐transplant outcomes with sufficient accuracy to support routine clinical use. Further studies with larger samples and more robust methodology are needed. (PROSPERO registration: CRD42019121161).